Assessment of Vegetation Condition Change and Impacts of Human Activities in Guanzhong Plain During 2000-2015: A Case of Xianyang City. (February 2019) - Yan, Nana; Zhu, Weiwei; Ma, Zonghan; Wu, Bingfang
Abstract: The agricultural production in Guanzhong Plain plays an important role in food security, ecological environment and socio-economic sustainable development in the Loess Plateau. Taking Xianyang City as an example, this paper analyzed the responses of vegetation condition to meteorological factors, particularly for crop growth period, and distinguished the contribution rate of climate and human activities for different periods. The results showed that the average slope of NDVI change trend in the vegetation area of Xianyang City was 0.005/year from 2000 to 2015. The northern part showed a significant growth trend of NDVI, while the south was mixed. NDVI in spring was significantly correlated with temperature and wind speed. The relative contribution rates of human activities to crop condition changes were 58.3%; NDVI during July-September was significantly correlated with wind speed and precipitation. The relative contribution rate of human activities reached 66.1%.